Drivers of Cryptocurrency Adoption in Iran: Evidence from the Baluchistan Region - Karimzadeh, Majid; Yousefi, Farzad; Goldarzehi, Razieh; Delgarm, Atefeh (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: This study explores the key factors influencing the acceptance of cryptocurrencies in Iran, focusing on the under-researched Baluchistan region. In contrast to previous studies focusing on developed or technologically advanced economies, this research explores a socioeconomically disadvantaged region experiencing economic instability and restricted access to formal financial services. Research Objectives: The main goal of the study is to identify and analyze the key factors influencing cryptocurrency acceptance in this region. Research Methods: Using data from 200 active cryptocurrency users, we employed exploratory factor analysis followed by multiple regression analysis to identify and test predictive factors. Empirical Results: The findings reveal six primary drivers: financial constraints, national economic volatility, personality traits, social influences, managerial factors, and trust. Among these, income-related motivations and macroeconomic instability emerged as the strongest predictors of adoption. Implications: The study contributes to the literature by contextualizing cryptocurrency behavior within a developing country’s marginalized setting and provides insights for policymakers to enhance financial inclusion. It also highlights the need for regulatory clarity and user education to support safe and effective participation in digital finance. JEL Classification: G1, G4, G10, G41